A new species of Holangus Pic, 1902 (Coleoptera, Cerambycidae, Cerambycinae) from Hubei, China - Wang, Ping; Xie, Guanglin; Wang, Wenkai (Zootaxa, 2020)
Holangus shennongjiaensis sp. nov. from Shennongjia Forestry District, Hubei, China is described and illustrated.